The correlation between electronic structure and antimalarial activity of tetrahydropyridines - Naranjo-Montoya, Oscar A.; Martins, Lucas M. [UNESP]; Silva-Filho, Luiz C. da [UNESP]; Batagin-Neto, Augusto [UNESP]; Lavarda, Francisco C. [UNESP] (Soc Brasileira Quimica, 2015)
In this study, correlations between electronic structure and the antimalarial activities reported for a group of 21 tetrahydropyridines were evaluated by multivariate methods. Simple and multiple linear regressions, principal component analyses, and linear discriminant analyses were employed to evaluate possible correlations between quantum-mechanical descriptors and pharmacological activity. The results obtained provide useful information on the position of active sites of tetrahydropyridines and identify some specific features associated with active derivatives. Based on these findings, simple substitution rules are proposed for designing more efficient tetrahydropyridine derivatives.
Keywords: Antimalarials; Tetrahydropyridines; Electronic structure; Molecular modeling; Quantitative structure-activity relationship